Relativization in Swedish - Dora Maček (Linguistica, 1987)
Relativization is a widespread syntactic and pragmatic strategy, found in such di verse languages as Arabic and Korean, Nahuatl and German (The Chicago Which Which Hunt 1972). It is a process of modifier formation producing relative clauses (RC), which can serve several pragmatic functions, such as supplying new informa tion, emphasis, cohesion etc. RCs have been much studied and they still offer intere sting linguistic insights. Alongside the obviously common features many differences in detail can be observed even among closely related languages. The differences as well as the similarities can be of a syntactic or a stylistic nature. Out of the many in teresting aspects of RC structure and usage a closer look will be taken only at the choice of the linking word and some rules governing its place and function.